Aplikasi Pemberian Abu Sekam Padi dan Pupuk Organik Cair (POC) Terhadap Produksi Tanaman Cabai Merah (Capsicum annum L.) - Nur Ilham; Novilda Elizabeth Mustamu; Badrul Ainy Dalimunthe; Siti Hartati Yusida Saragih (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2023)
Indonesia is an agricultural country where the majority of the population makes a living as farmers. This is supported by the large amount of vacant land that can be used as agricultural land, in addition to the condition of the soil in Indonesia which has good nutrient content so that it can help plant growth. One of the leading horticultural products in the agricultural sector in Indonesia is vegetable crops. One of the vegetable commodities needed by almost all industries is chili. Red chili plant is one type of vegetable that has a fairly high water content (55-85%) at the time of harvest. In addition to still experiencing the respiration process, red chili peppers will experience a process of wilting. . The supply of red chili peppers is often unable to meet market demand, resulting in the price of red chili peppers soaring in the market. The high price of red chili is one of the causes of inflation. Good soil conditions for the growth of red pepper plants are sandy loam, because with these soil conditions it can bear fruit quickly while on clay soils it tends to be a bit slow, therefore Rice Husk Ash is needed to improve the soil foundation. Rice husk ash serves to loosen the soil so that it can make it easier for plant roots to absorb nutrients in it. Fertilizer plays an important role in increasing plant yields, one of which is liquid organic fertilizer from household waste, the benefits of liquid organic fertilizer, especially in soils with low nutrient content so that it can improve nutrient properties and add nutrients that are present and needed in the soil in order to obtain the growth behavior of the Red Chili plant (Capsicum annum L.). Therefore, I conducted this research to be able to improve the chemical properties of peat soil by applying rice husk ash and liquid organic fertilizer household waste to see growth in red chili plants (Capsicum annum L.). Keywords: Red Chili, rice husk ash, Liquid Organic Fertilizer (POC).